Prospective association between standing balance and cognitive function in middle-aged and older Chinese adults - Yan, Jingzheng; Luan, Fangyun; Wang, Meijuan; Dong, Wenshuo; Zhang, Xinyue; Li, Mengli; Cao, Yingjuan (Frontiers in Psychology, 2022)
Abstract Objective: To investigate the association of standing balance with cognitive functions and rates of cognitive decline among middle-aged and older Chinese adults. Methods: Participants were selected from China’s Health and Retirement Longitudinal Study. A total of 8,499 subjects aged ≥45 years who participated in wave 1 to wave 3 surveys were included in the final analysis. Standing balance was measured using the tandem test, and participants were categorized into two groups according to completion status. Cognitive functions were assessed in three domains: episodic memory, mental status, and global cognition. The associations between balance tests , cognitive scores, and rates of cognitive decline were evaluated using linear regression and linear mixed models. Results: Compared with participants who did not complete the balance test, those who completed the test had higher scores on episodic memory (β=0.18; 95% confidence interval [CI]: 0.11, 0.24), mental status (β=0.28; 95% CI: 0.19, 0.37), and global cognition (β=0.51; 95% CI: 0.38, 0.65) after 4 years of follow-up. In addition, the rate of decline in mental status and global cognition decreased by 0.10 (β=-0.10; 95% CI: -0.13, -0.07) and 0.08 (β=-0.08; 95% CI: -0.12, -0.04) units, respectively, in participants who completed the test compared with their counterparts. Conclusion: Good standing balance was significantly associated with good cognitive function and a slower decline in mental status and global cognition scores in middle-aged and older Chinese adults.